Convective Porous Medium Systems with Nonlinear Forcing at the Boundary (Journal of Partial Differential Equations, 1999)
This paper deals with the global positive solutions of convective porous medium systems with nonlinear forcing at the boundary. Necessary and sufficient conditions on the global existence of all positive solutions are obtained.
Keywords: Convective porous medium systems; nonlinear boundary conditions; global solution; blow up; upper and lower solutions methods